A Negishi Approach to Recursive Contracts - Bloise, Gaetano; Siconolfi, Paolo (Econometrica, 2022)
In this paper, we argue that a large class of recursive contracts can be studied by means of the conventional Negishi method. A planner is responsible for prescribing current actions along with a distribution of future utility values to all agents, so as to maximize their weighted sum of utilities. Under convexity, the method yields the exact efficient frontier. Otherwise, the implementation requires contracts be contingent on publicly observable random signals uncorrelated to fundamentals. We also provide operational first‐order conditions for the characterization of efficient contracts. Finally, we compare extensively our approach with the dual method established in the literature.